Ensino de estudantes público da educação especial em uma escola ribeirinha amapaense - Lima, Ilene Diniz Sacramento (Universidade Federal de São Carlos, 2024)
This research is focused on the socio-educational reality of Public Special Education students in a riverside school in Amapá, linked to the Municipal Education System. Its general objective is to analyze the teaching process of Public Special Education students who attended a riverside school and the specific objectives are: a) to characterize the pedagogical practices of the teacher of specialized educational services in the teaching process of Public Special Education students; b) describe the teaching process of the teacher directed towards Public Special Education students enrolled and attending regular education at a riverside school; c) analyze the relationship between Special Education teacher and common room teacher. The main element of the investigative context of this work is the interest in knowledge of pedagogical practices for Public Special Education students. It is an ethnographic study with an emphasis on education. The procedures that denoted the methodological basis of this work were semi-structured interviews, participant observation and document analysis. There were six research subjects, namely a Special Education teacher, four regular class teachers and a pedagogical coordinator. Regarding the results, it was evident that few productions involve the theme of this dissertation in this Amazon region; there was a high demand from Public Special Education students for the Special Education teacher on the grounds that she was a full-time teacher; there were reports of absence of parents in partnership with the school, lack of resources for the teaching process to be more optimized, lack of adaptations in textbooks, lack of training for common classroom teachers, structures of the main and annex buildings requiring repairs and the even more serious annex, due to leaks and, in times of rain, classes are canceled due to this factor. Absence of Political Pedagogical Project (PPP). It was evident that Public Special Education students were well accepted and received attention from both their classmates and teachers and that, despite all the difficulties and obstacles, the participants enjoyed working on the island. With the result, we sought to give greater visibility to the diversity of riverside people and the interface of Special Education and rural education, in the context of riverside schools.
Teaching public special education students in a riverside school in Amapá
Keywords: Educação especial ribeirinha; Ensino de estudantes público da educação especial; Educação do campo; Special riverside education; Teaching public special education students; Rural education; CIENCIAS HUMANAS::EDUCACAO